Paradoxical effects of temperature in multiple sclerosis. Issue 9 (September 1987) - Honan, W P; Heron, J R; Foster, D H; Snelgar, R S
Abstract : Six cases of multiple sclerosis are reported in which cold produced a temporary exacerbation of symptoms and signs of the disease. Also, in one case investigated in detail by psychophysical methods, heating produced a paradoxical deterioration in vision and simultaneous improvement in sensory and motor function. The effect of temperature in multiple sclerosis is discussed and a physiological explanation for the paradoxical response to heating is suggested.